Marketing Strategy in Improving Product Competitiveness in the Global Market - Sudirjo, Frans (ADMAN: Journal of Contemporary Administration and Management, 2023)
The global market is an increasingly competitive and dynamic business environment. Technological developments, globalisation, and internet access have changed consumer patterns and opened up opportunities and challenges for companies in marketing their products internationally. In such a market environment, companies are required to have effective marketing strategies in order to increase the competitiveness of their products in the global market. This research aims to examine marketing strategies in improving product competitiveness in the global market. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that the global market offers great opportunities for companies to achieve growth and success at the international level. However, fierce competition and complex market dynamics also require companies to have the right marketing strategy.